Circular economy and technological innovation : the regional implications - Khan, Syed Abdul Rehman, 1987-; Sheikh, Adnan Ahmed; Kolade, Oluwaseun; Kamble, Sachin (Singapore : Springer, 2025)
This book explores the circular economy, its context, methodology, and commercial strategies, with a focus on waste minimization, recycling, green marketing, and sustainable business practices to facilitate resource recovery. It considers IR 4.0 and 5.0 to show how smart technology innovation extends circular economy through industrial organizational sustainability and investigates circular economy technology innovation in multiple scenarios to exploit product re-usability and technological innovation in Asian, European, and Australian contexts. It discusses novel digital technologies such as blockchain, additive manufacturing, AI, ML, and IoT for global supply chain tracking. This book is valuable for instructors and students in business, environmental studies, supply chain management, product re-manufacturing, and marketing programs seeking cutting-edge Circular Economy and Technological Innovation trends.
Kolektivní monografie představuje aktuální pohled na cirkulární ekonomiku v kontextu technologických inovací. Zaměřuje se na strategie snižování odpadu, recyklaci, udržitelné podnikání a využití digitálních technologií (AI, blockchain, IoT, aditivní výroba) pro sledování a optimalizaci globálních dodavatelských řetězců. Autoři propojují koncept cirkulární ekonomiky s průmyslovými trendy IR 4.0 a 5.0 a ukazují jeho dopady v asijském, evropském i australském prostředí. Kniha je určena studentům, pedagogům i odborníkům v oblasti environmentálních studií, supply chain managementu a udržitelného podnikání.
Obsahuje bibliografické odkazy
Keywords: cirkulární ekonomika; environmentální ekonomie; recyklace odpadu; udržitelný rozvoj; udržitelná spotřeba a výroba; společenská odpovědnost firem; inovace; digitální transformace; kolektivní monografie; circular economy; environmental economics; waste recycling; sustainable development; sustainable consumption and production; corporate social responsibility; innovations; digital transformation; collective monographs